The U.S. Military Response to the 2010 Haiti Earthquake Considerations for Army Leaders - Cecchine, Gary (RAND Corporation, 2013)
This report examines how Joint Task Force-Haiti (JTF-Haiti) supported the humanitarian assistance and disaster relief efforts in Haiti. It focuses on how JTF-Haiti was organized, how it conducted Operation Unified Response, and how the U.S. Army supported that effort. The analysis includes a review of existing authorities and organizations and explains how JTF-Haiti fit into the U.S. whole-of-government approach and the international response.